College algebra : - Steffensen, Arnold L. (Addison-Wesley, 1996)
This book introduction the nature of mathematics, the set of integers, the set of rational numbers, the set of real numbers, the set of comlex numbers, equations and inequalities, functions and their graphs, systems of equations